MANAJEMEN PROGRAM MARKET DAY DI SEKOLAH DASAR - Ningrum, Faradita Ersanti; Nugroho, Piter Joko; Purnomo, Widiharto (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2024)
This study aims to describe the Market Day Program Management at SDIT Alam IKM Al-Muhajirin Palangka Raya. This research uses a qualitative approach. The data sources were the Principal, Vice Principal and Grade 6 students. Data collection techniques were observation, interview and study of document. Data analysis uses an interactive data model, including: (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion drawing. Checking the validity of the data in this study using triangulation and member check. The results showed that the management of the market day program which is carried out effectively becomes a means of developing Islamic entrepreneurial character which is very useful for the future of students.